The Safety and Efficacy of Live Viral Vaccines in Patients With Cartilage-Hair Hypoplasia - Vakkilainen, Svetlana; Kleino, Iivari; Honkanen, Jarno; Salo, Harri; Kainulainen, Leena; Gräsbeck, Michaela; Kekäläinen, Eliisa; Mäkitie, Outi; Klemetti, Paula (Frontiers in Immunology, 2020)
Background: Live viral vaccines are generally contraindicated in patients with combined immunodeficiency including cartilage-hair hypoplasia (CHH); however, they may be tolerated in milder syndromes. We evaluated the safety and efficacy of live viral vaccines in patients with CHH. Methods: We analyzed hospital and immunization records of 104 patients with CHH and measured serum antibodies to measles, mumps, rubella, and varicella zoster virus (VZV) in all patients who agreed to blood sampling (n=50). We conducted a clinical trial (ClinicalTrials.gov identifier: NCT02383797) of live VZV vaccine on five subjects with CHH who lacked varicella history, had no clinical symptoms of immunodeficiency, and were seronegative for VZV; humoral and cellular immunologic responses were assessed post-immunization. Results: A large proportion of patients have been immunized with live viral vaccines, including measles-mumps-rubella (n=40, 38%) and VZV (n=10, 10%) vaccines, with no serious adverse events. Of the 50 patients tested for antibodies, previous immunization has been documented with MMR (n=22), rubella (n=2) and measles (n=1) vaccines. Patients with CHH demonstrated seropositivity rates of 96%/75%/91% to measles, mumps and rubella, respectively, measured at a medium of 24 years post-immunization. Clinical trial participants developed humoral and cellular responses to VZV vaccine. One trial participant developed post-immunization rash and knee swelling, both resolved without treatment. Conclusions: No serious adverse events have been recorded after immunization with live viral vaccines in Finnish patients with CHH. Patients generate humoral and cellular immune response to live viral vaccines. Immunization with live vaccines may be considered in selected CHH patients with no or clinically mild immunodeficiency.